2010
DOI: 10.1124/jpet.110.170472
|View full text |Cite
|
Sign up to set email alerts
|

A Transmembrane Amino Acid in the GABAA Receptor β2 Subunit Critical for the Actions of Alcohols and Anesthetics

Abstract: Alcohols and inhaled anesthetics enhance the function of GABA A receptors containing ␣, ␤, and ␥ subunits. Molecular analysis has focused on the role of the ␣ subunits; however, there is evidence that the ␤ subunits may also be important. The goal of our study was to determine whether Asn265, which is homologous to the site implicated in the ␣ subunit (Ser270), contributes to an alcohol and volatile anesthetic binding site in the GABA A receptor ␤ 2 subunit. We substituted cysteine for Asn265 and exposed the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
(51 reference statements)
3
32
1
Order By: Relevance
“…Thus, in parallel to recent studies of GlyRs (Crawford et al, 2007) and nAChRs (Borghese et al, 2003), MTS reagents can be valuable tools for discriminating between multiple sites of alcohol interaction: substitution and labeling of our target residue revealed an inhibitory effect previously masked by the potentiating effects of alcohols at other sites in the same receptor. Furthermore, in parallel to recent work on the 15Ј potentiating site (McCracken et al, 2010), we showed that coapplication of methanol blocked the inhibitory effect of MMTS on the 6Ј cysteine mutant. This result is consistent with direct jpet.aspetjournals.org competition for a 6Ј-proximal inhibitory binding site, although we cannot exclude the possibility that allosteric modification of the receptor renders the 6Ј site inaccessible to MMTS.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, in parallel to recent studies of GlyRs (Crawford et al, 2007) and nAChRs (Borghese et al, 2003), MTS reagents can be valuable tools for discriminating between multiple sites of alcohol interaction: substitution and labeling of our target residue revealed an inhibitory effect previously masked by the potentiating effects of alcohols at other sites in the same receptor. Furthermore, in parallel to recent work on the 15Ј potentiating site (McCracken et al, 2010), we showed that coapplication of methanol blocked the inhibitory effect of MMTS on the 6Ј cysteine mutant. This result is consistent with direct jpet.aspetjournals.org competition for a 6Ј-proximal inhibitory binding site, although we cannot exclude the possibility that allosteric modification of the receptor renders the 6Ј site inaccessible to MMTS.…”
Section: Discussionsupporting
confidence: 62%
“…Having tested a variety of ␣2␤2 mutants, we extended this work by showing that tryptophan substitution at ␣2(Thr6Ј) also reduces alcohol potentiation of ␥-containing receptors, which are the predominant population in brain (Möhler, 2006). Furthermore, although many structure/function studies on alcohol modulation have focused on GABA A R ␣ subunits (Mascia et al, 2000), McCracken et al (2010) recently demonstrated a critical role for the TM2 15Ј position in the GABA A R ␤2 subunit in receptor potentiation by alcohols and anesthetics. We also showed conservation of the inhibitory effect of MMTS labeling at the 6Ј position in ␣2 and ␤2 subunits, again in the context of ␥-containing receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Bali and Akabas (50) introduced cysteine at two β2 positions, β2N265 and β2M286, where other mutations were known to influence propofol sensitivity in α1β2γ2 receptors (Figure 6 shows these residues in β3, which is highly homologous to β2 in this region). Both residues are predicted to contribute to the “β + ” transmembrane interface, although β2N265 may also be accessible from the “β − ” interfacial pocket (51). To achieve comparable mixes of receptor states during control and protection experiments, Bali and Akabas used a strategy different from ours, likely resulting in under 50% anesthetic site occupancy.…”
Section: Anesthetic Scamp Results In Gabaarsmentioning
confidence: 99%
“…Oocytes from female X. laevis frogs were extracted, isolated, and stored as described previously elsewhere (McCracken et al, 2010;Howard et al, 2011). For the expression of GLIC, 32 nl cDNA solution was injected into the oocyte nucleus via the animal pole using a microdispenser (Drummond Scientific, Broomall, PA) with a 20-30 mm outer diameter glass capillary tip pulled with a Flaming/Brown Micropipette Puller (Sutter Instrument Co., Novato, CA).…”
Section: Validation Of Virtual Screening For Anesthetics Inmentioning
confidence: 99%